PENGARUH UKURAN PERUSAHAAN, PERTUMBUHAN PENJUALAN, PROFITABILITAS DAN LIKUIDITAS TERHADAP STRUKTUR MODAL: Studi Kasus pada Perusahaan Subsektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2020 - Ervina Yulia Ningrum; Khairunnisa Khairunnisa (Universitas Pasundan, 2022)
Competition in the business world is getting higher, every company wants to keep the company afloat. For organizations to get by, organizations need ventures through financing choices. Companies have alternatives from internal and external. In this case, the capital structure is important to a company because capital is the foundation of the company to build and keep a company alive. Reason for This review to decide the concurrent and fractional impact on company size, sales growth, profitability and liquidity on the capital structure of food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2016-2020. This study uses quantitative methods, sample selection techniques using purposive sampling, hypothesis testing using panel data. The consequences of this study show that organization size, deals development, benefit and liquidity all the while influence the capital design. To some degree, just organization size and liquidity adversely affect capital construction.